Comparative Growth and Yield of Multipurpose Trees in Semi-arid Natural Grassland - Raj, P; Rao, G R; Solanki, K R; Ramana, D B V (Annals of Arid Zone, 2016)
Studies on comparative growth and production of 12 multipurpose tree species (MPTS) from 1988 to 1995 under Dichallthilllll alllllllatwn-dominated natural grassland revealed that 6 trees viz., Albizia alllara, A. lebbek, Acacia tortilis, Dichrostachys cillerea, Lellcaella lellcocephala and POllgalllia pillilata had better rowth (leaf fodder and fuel wood) and production, as well as higher crude protein In leaf fodder under this agro-c1imatic region. Thus, the above six MPTS are suitable for introduction in such type of grassland for getting the higher and nutritious leaf fodder as well as fuel wood.